Respuesta :

Step-by-step explanation:

Hope it helps man .....

Ver imagen BishrantBaral

Answer:

J-¹(x)= x+6/5

or

J-¹(x)= x/5 + 6/5

Step-by-step explanation:

J(x)= 5x -6

•first separate your Y from the original equation like this

y= 5x-6

•second replace for x since we are talking about the inverse form

x= 5y-6

•third solve for y

x+6=5y-6+6

add 6 to both sides

x+6=5y

divide 5 to both sides

x+6/5=5y/5 (in your right side 5 cancels out)

it should look like this

x+6/5=y (you solved for y)

and now you write your answer like this

J-¹(x)= x+6/5

or

J-¹(x)= x/5 + 6/5